TiO2 / Mn-V2O2 / SiO2 composite film as well as preparation method and application thereof

By using a TiO2/Mn-VO2/SiO2 composite thin film structure and preparation process, the problem of high VO2 phase transition temperature has been solved, achieving applicability and performance improvement in daily environments, making it suitable for smart window applications.

CN121700375APending Publication Date: 2026-03-20FOSHAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511887243.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-15
Publication Date
2026-03-20

AI Technical Summary

Technical Problem

The phase transition temperature of pure VO2 is much higher than the human body's comfortable temperature range, which cannot meet the needs of daily indoor use. It needs to be modified to reduce its phase transition temperature while maintaining its thermochromic properties.

Method used

A TiO2/Mn-VO2/SiO2 composite thin film structure was adopted. Through the synergistic effect of the SiO2 buffer layer and TiO2 functional layer and the Mn-doped VO2 first functional layer, the phase transition temperature was reduced and the optical and thermal properties were improved. The film was prepared by combining the sol-gel method and spin coating-annealing process.

Benefits of technology

The composite film achieves adaptability within the normal temperature range, improves visible light transmittance, solar irradiance regulation efficiency and self-cleaning function, enhances the structural stability and interfacial adhesion of the film, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121700375A_ABST
    Figure CN121700375A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermochromic films, and discloses a TiO2 / Mn-VO2 / SiO2 composite film and a preparation method and application thereof.The TiO2 / Mn-VO2 / SiO2 composite film sequentially comprises a buffer layer, a first functional layer and a second functional layer; wherein the buffer layer is formed by SiO2; the first functional layer is formed by a first material, the first material is obtained by doping VO2 with Mn, and the doping amount of Mn is 0.8 at.%-1.2 at.%; the second functional layer is formed of TiO2. The TiO2 / Mn-VO2 / SiO2 composite film structure is constructed, and by virtue of the synergistic effect of Mn doping, the SiO2 buffer layer and the TiO2 functional layer, the phase change temperature of the thermochromic material is effectively reduced to adapt to daily use scenes, and meanwhile, excellent visible light transmittance and solar irradiation regulation efficiency are comprehensively guaranteed; and the practical functions of interface adhesion, structural stability, self-cleaning and the like of the film are remarkably improved, and comprehensive optimization of core performance and use characteristics is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermochromic thin film technology, and specifically relates to a TiO2 / Mn-VO2 / SiO2 composite thin film, its preparation method and application. Background Technology

[0002] The energy crisis and energy conservation and emission reduction have become core issues for global sustainable development. Building energy consumption, as a key component of global total energy consumption, accounts for as much as 40%. Windows, as the main channel for heat exchange between buildings and the outside world, account for nearly 60% of the total energy loss in buildings, making them a key breakthrough point for building energy conservation. Against this backdrop, smart windows have emerged with their core characteristic of dynamically regulating solar radiation energy. They can automatically switch optical states according to changes in ambient temperature, maintaining the indoor environment within a comfortable temperature range for humans, thereby significantly reducing the energy consumption of heating and cooling systems and becoming one of the key technologies for improving building energy efficiency.

[0003] Among various smart window technologies, thermochromic smart windows have become a key research and development direction for commercial applications due to their lack of need for additional driving energy, sensitive response, and simple structure. Vanadium dioxide (VO2), as a typical thermochromic material, undergoes a reversible metal-semiconductor transition (MST) at a phase transition temperature (Tc) of approximately 68°C. The transmittance in the near-infrared band (780-2650nm) before and after the phase transition shows a significant difference. At low temperatures (below Tc), it is a semiconductor phase with high transmittance to near-infrared light, allowing for the transfer of solar heat; at high temperatures (above Tc), it is a metallic phase with high reflectivity to near-infrared light, blocking external heat intrusion. Its transmittance in the visible light band (380-780nm) remains relatively stable. Therefore, it is considered the optimal candidate material for thermochromic smart window coatings.

[0004] However, the phase transition temperature of pure VO2 (68℃) is much higher than the human comfort temperature range (20-26℃), which cannot meet the needs of daily indoor use. It is necessary to modify it to reduce its phase transition temperature. Therefore, it is necessary to find an effective solution that takes into account both phase transition temperature regulation and thermochromic core performance. Summary of the Invention

[0005] The present invention aims to improve at least one technical problem in the prior art.

[0006] The first aspect of the present invention provides a TiO2 / Mn-VO2 / SiO2 composite thin film, comprising a buffer layer, a first functional layer and a second functional layer in sequence; The buffer layer is formed of SiO2; The first functional layer is formed of a first material, which is obtained by doping Mn with VO2, wherein the doping amount of Mn is 0.8 at.% to 1.2 at.%. The second functional layer is formed of TiO2.

[0007] The TiO2 / Mn-VO2 / SiO2 composite thin film provided in this application is composed of a buffer layer, a first functional layer, and a second functional layer, arranged sequentially. The selection and combination of materials in each layer work synergistically to ensure the thermochromic performance and practical characteristics of the composite thin film. The buffer layer uses SiO2, which optimizes the interfacial bonding with the glass substrate, providing a stable and flat substrate environment for the growth of the first functional layer. It also helps improve the overall structural stability of the thin film, laying the foundation for the subsequent thermochromic performance. The first functional layer is made of VO2 doped with Mn. The ionic crystal radius and ionic radius of Mn are similar to those of V, and this structural similarity allows Mn to be easily integrated into the VO2 lattice for efficient doping, effectively reducing the phase transition temperature of VO2. This allows the composite thin film to adapt to daily indoor and outdoor temperature changes, meeting the practical needs of smart windows. Furthermore, the Mn doping amount is controlled within a specific range of 0.8 at.% to 1.2 at.%, which better balances the phase transition temperature control with the stability of the thin film's optical and thermal properties. The second functional layer uses TiO2 material, which combines hydrophobic properties with anti-reflective functions. On the one hand, it reduces the reflection loss of external light and improves visible light transmittance; on the other hand, it forms a hydrophobic surface, reducing dust adhesion and facilitating rainwater rinsing for a self-cleaning effect. Simultaneously, it effectively protects the internal first functional layer and buffer layer, extending the service life of the entire composite film. The rational selection and synergistic design of the materials in each layer of this application give this composite film excellent potential as the core coating of a smart window.

[0008] Preferably, the thickness of the buffer layer is 70nm~100nm, the thickness of the first functional layer is 70nm~100nm, and the thickness of the second functional layer is 70nm~100nm.

[0009] A second aspect of the present invention provides a method for preparing the above-mentioned TiO2 / Mn-VO2 / SiO2 composite thin film, wherein the SiO2 precursor solution is prepared from the SiO2 by a sol-gel method, the first material precursor solution is prepared from the first material by a sol-gel method, and the TiO2 precursor solution is prepared from the TiO2 by a sol-gel method; the preparation method includes the following steps: The SiO2 precursor liquid is spin-coated onto the surface of the substrate, and then subjected to a first annealing to form the buffer layer; The first material precursor liquid is spin-coated onto the surface of the buffer layer, and then subjected to a second annealing to form the first functional layer; The TiO2 precursor liquid is spin-coated onto the surface of the first functional layer, and then subjected to a third annealing to form the second functional layer, thereby obtaining the TiO2 / Mn-VO2 / SiO2 composite film.

[0010] The TiO2 / Mn-VO2 / SiO2 composite film preparation method provided in this application is based on a combination of sol-gel method and spin-coating-annealing process. By precisely controlling the preparation process of each layer, the composite film is constructed in an orderly manner. The process is simple and suitable for large-scale production. The sol-gel method has the advantages of a mild preparation process, easy control of the precursor solution composition, and good film uniformity. It is used to prepare the SiO2 precursor solution, the first material precursor solution, and the TiO2 precursor solution, respectively, ensuring the purity and dispersion stability of each layer, laying the foundation for subsequent film performance. In the preparation process, SiO2 precursor liquid is first spin-coated onto the substrate surface and then subjected to a first annealing to form a buffer layer. This step allows the SiO2 precursor liquid to spread and solidify fully, forming a transition layer that is tightly bonded to the substrate. Subsequently, a first material precursor liquid is spin-coated onto the surface of the buffer layer and then subjected to a second annealing to form a first functional layer, allowing the manganese-doped VO2 material to fully crystallize, ensuring the phase transition temperature control effect and thermochromic performance. Finally, TiO2 precursor liquid is spin-coated onto the surface of the first functional layer and then subjected to a third annealing to form a second functional layer, enabling the TiO2 material to form a dense thin film with both hydrophobic and anti-reflective properties.

[0011] The spin coating of the SiO2 precursor liquid includes a first spin coating and a second spin coating. The first spin coating rate is 300 r / min to 500 r / min and the first spin coating time is 6 s. The second spin coating rate is 3000 r / min to 6000 r / min and the second spin coating time is 30 s.

[0012] The spin coating of the first material precursor liquid includes a third spin coating and a fourth spin coating in sequence. The third spin coating rate is 300 r / min to 500 r / min and the third spin coating time is 6 s. The fourth spin coating rate is 3000 r / min to 6000 r / min and the fourth spin coating time is 30 s.

[0013] The spin coating of the TiO2 precursor liquid includes a fifth spin coating and a sixth spin coating in sequence. The fifth spin coating rate is 300 r / min to 500 r / min and the fifth spin coating time is 6 s. The sixth spin coating rate is 3000 r / min to 6000 r / min and the sixth spin coating time is 30 s.

[0014] In this application, the spin coating of the SiO2 precursor solution, the first material precursor solution, and the TiO2 precursor solution are all performed in a two-step spin coating process. First, a low-speed spin coating allows the corresponding precursor solution to slowly spread on the substrate or the surface of the previous thin film layer, ensuring uniform coverage of the entire area to be coated and avoiding problems such as localized missed coating or droplet aggregation. This lays the foundation for the subsequent formation of a continuous and dense thin film. Then, a high-speed spin coating utilizes centrifugal force to remove excess precursor solution while controlling the final thickness of the film, keeping the thickness of each layer within the target range and ensuring a smooth and uniform surface. This two-step spin coating process avoids the problems of excessive film thickness and decreased light transmittance caused by low-speed spin coating, while also preventing defects such as uneven precursor solution distribution and film cracking caused by high-speed direct spin coating. This ensures the structural consistency of each thin film layer, thereby synergistically improving the overall optical and thermochromic properties of the composite film.

[0015] The first annealing temperature is 400℃~550℃ and the time is 1h~2h; the second annealing temperature is 400℃~550℃ and the time is 1h~2h; the third annealing temperature is 400℃~550℃ and the time is 1h~2h.

[0016] This application can promote the full evaporation of solvent in the precursor solution during the annealing process, allowing each layer of material to be completely cured, forming a dense solid film, improving the mechanical strength and interlayer adhesion of the film, and avoiding problems such as peeling and cracking during use; at the same time, this temperature can induce the Mn-doped VO2 material to fully crystallize, ensuring that the Mn element is stably integrated into the VO2 lattice, ensuring the control effect of the phase transition temperature, and preventing the material from oxidizing or lattice distortion due to excessively high temperature, nor causing insufficient crystallization and unstable performance due to excessively low temperature.

[0017] The preparation of the first material precursor solution includes the following steps: The vanadium and manganese sources were dissolved in water, and polyvinylpyrrolidone was added and stirred to obtain the precursor solution of the first material.

[0018] Preferably, the substrate is obtained after cleaning and drying.

[0019] Preferably, the substrate is fixed by a suction cup, and the vacuum degree of the suction cup is 3×10⁻⁶. -2 Pa~2×10 -1 Pa.

[0020] The third aspect of the present invention provides the application of the above-mentioned TiO2 / Mn-VO2 / SiO2 composite film in smart windows.

[0021] The beneficial effects of this invention are as follows: By constructing a TiO2 / Mn-VO2 / SiO2 composite thin film structure, and leveraging the synergistic effect of Mn doping, the SiO2 buffer layer, and the TiO2 functional layer, this invention effectively reduces the phase transition temperature of thermochromic materials to suit everyday use scenarios, while comprehensively ensuring excellent visible light transmittance and solar irradiance regulation efficiency. It also significantly improves the film's interfacial adhesion, structural stability, and self-cleaning capabilities, achieving comprehensive optimization of core performance and usage characteristics. Furthermore, the use of a sol-gel method combined with optimized spin coating and annealing processes not only ensures the uniformity and molding quality of the film but also offers advantages such as simple processing, low preparation cost, and low energy consumption. It eliminates the need for high-precision, high-cost equipment and process conditions, making it more suitable for large-scale industrial production. This provides a technical solution with both performance advantages and practical value for the commercial promotion of thermochromic smart windows, powerfully promoting the application of related technologies in the field of building energy conservation. Attached Figure Description

[0022] Figure 1 This is a light transmittance diagram of the TiO2 / Mn-VO2 / SiO2 composite film prepared in Example 1; Figure 2 The XRD pattern of the first functional layer in Test Example 1; Figure 3 The SEM image of the first functional layer in Test Example 1; Figure 4 This is the EDS diagram of the first functional layer in Test Example 1. Detailed Implementation

[0023] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the description of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0024] Example 1 A TiO2 / Mn-VO2 / SiO2 composite thin film comprises, in sequence, a buffer layer (thickness of 85 nm), a first functional layer (thickness of 82 nm), and a second functional layer (thickness of 88 nm); wherein the buffer layer is formed of SiO2; the first functional layer is formed of a first material (obtained by doping Mn with VO2, the doping amount of Mn is 1 at.%); and the second functional layer is formed of TiO2.

[0025] The preparation method of this TiO2 / Mn-VO2 / SiO2 composite thin film includes the following steps: The glass substrate is ultrasonically cleaned, then repeatedly cleaned with methanol, ethanol and deionized water, and then naturally dried. SiO2 precursor solution (80 μL / cm) 2 Spin-coating was applied to the surface of a glass substrate (first at 400 rpm for 6 seconds, then at 3000 rpm for 30 seconds; the glass substrate was fixed by a chuck with a vacuum of 3 × 10⁻⁶). -2 After drying for 10 minutes, the buffer layer is formed by annealing at 550°C for 1 hour under a nitrogen atmosphere. The first material precursor solution (78 μL / cm) 2 Spin-coat the buffer layer surface (first spin-coat at 400 r / min for 6 s, then spin-coat at 3000 r / min for 30 s), dry for 10 min, and then anneal at 550℃ for 1 h in a nitrogen atmosphere to form the first functional layer. TiO2 precursor solution (83 μL / cm) 2 The TiO2 / Mn-VO2 / SiO2 composite film was obtained by spin-coating the first functional layer onto the surface of the first functional layer (first spin-coating at 400 r / min for 6 s, then spin-coating at 3000 r / min for 30 s), drying for 10 min, and then annealing at 550 °C for 1 h in a nitrogen atmosphere to form the second functional layer.

[0026] The preparation of the SiO2 precursor solution includes the following steps: Ethyl orthosilicate, ethanol and deionized water are mixed in a volume ratio of 1:3:0.5, 0.1% polyvinylpyrrolidone is added, and the mixture is stirred at 80°C for 24 hours to obtain the SiO2 precursor solution. The preparation of the first material precursor solution includes the following steps: using ammonium metavanadate as the vanadium source (concentration 0.2mol / L) and manganese chloride as the manganese source (concentration 0.002mol / L), dissolving them in a mixed solvent of deionized water, adding 0.05% by mass of polyvinylpyrrolidone, and stirring at 60°C for 18h to obtain the first material precursor solution; The preparation of TiO2 precursor solution includes the following steps: Tetrabutyl titanate, isopropanol and deionized water are mixed in a volume ratio of 1:4:0.3, nitric acid is added dropwise to adjust the pH to 3-4, 0.08% polyvinylpyrrolidone is added, and the mixture is stirred at 60°C for 24 hours to obtain TiO2 precursor solution.

[0027] The light transmittance of the TiO2 / Mn-VO2 / SiO2 composite film prepared in Example 1 is shown in the figure below. Figure 1 As shown.

[0028] Example 2 A TiO2 / Mn-VO2 / SiO2 composite thin film comprises, in sequence, a buffer layer (75 nm thick), a first functional layer (72 nm thick), and a second functional layer (78 nm thick); wherein the buffer layer is formed of SiO2; the first functional layer is formed of a first material (obtained by doping Mn with VO2, the doping amount of Mn is 0.8 at.%); and the second functional layer is formed of TiO2.

[0029] The preparation method of this TiO2 / Mn-VO2 / SiO2 composite thin film includes the following steps: The glass substrate is ultrasonically cleaned, then repeatedly cleaned with methanol, ethanol and deionized water, and then naturally dried. SiO2 precursor solution (85 μL / cm) 2 Spin-coating was applied to the surface of a glass substrate (first at 300 rpm for 6 seconds, then at 6000 rpm for 30 seconds; the glass substrate was fixed by a chuck with a vacuum of 3 × 10⁻⁶). -2 After drying for 10 minutes, the buffer layer is formed by annealing at 450°C for 2 hours under a nitrogen atmosphere. The first material precursor solution (82 μL / cm) 2 Spin-coat the buffer layer surface (first spin-coat at 300 r / min for 6 s, then spin-coat at 6000 r / min for 30 s), dry for 10 min, and then anneal at 450℃ for 2 h in a nitrogen atmosphere to form the first functional layer. TiO2 precursor solution (86 μL / cm) 2 The TiO2 / Mn-VO2 / SiO2 composite film was obtained by spin-coating the first functional layer onto the surface of the first functional layer (first spin-coating at 300 r / min for 6 s, then spin-coating at 6000 r / min for 30 s), drying for 10 min, and then annealing at 450 °C for 2 h in a nitrogen atmosphere to form the second functional layer.

[0030] The preparation of SiO2 precursor solution, first material precursor solution and TiO2 precursor solution is the same as in Example 1.

[0031] Example 3 A TiO2 / Mn-VO2 / SiO2 composite thin film comprises, in sequence, a buffer layer (90 nm thick), a first functional layer (87 nm thick), and a second functional layer (93 nm thick); wherein the buffer layer is formed of SiO2; the first functional layer is formed of a first material (obtained by doping Mn with VO2, the doping amount of Mn is 1.2 at.%); and the second functional layer is formed of TiO2.

[0032] The preparation method of this TiO2 / Mn-VO2 / SiO2 composite thin film includes the following steps: The glass substrate is ultrasonically cleaned, then repeatedly cleaned with methanol, ethanol and deionized water, and then naturally dried. SiO2 precursor solution (75 μL / cm) 2 Spin-coating was applied to the surface of a glass substrate (first at 500 rpm for 6 seconds, then at 4000 rpm for 30 seconds; the glass substrate was fixed by a chuck with a vacuum of 3 × 10⁻⁶). -2 After drying for 10 minutes, the mixture is annealed at 400°C for 1.5 hours under a nitrogen atmosphere to form a buffer layer. The first material precursor solution (73 μL / cm) 2 Spin-coat the buffer layer surface (first spin-coat at 500 r / min for 6 s, then spin-coat at 4000 r / min for 30 s), dry for 10 min, and then anneal at 400℃ for 1.5 h in a nitrogen atmosphere to form the first functional layer. TiO2 precursor solution (78 μL / cm) 2 The TiO2 / Mn-VO2 / SiO2 composite film was obtained by spin-coating the first functional layer onto the surface of the first functional layer (first spin-coating at 500 r / min for 6 s, then spin-coating at 4000 r / min for 30 s), drying for 10 min, and then annealing at 400 °C for 1.5 h in a nitrogen atmosphere to form the second functional layer.

[0033] The preparation of SiO2 precursor solution, first material precursor solution and TiO2 precursor solution is the same as in Example 1.

[0034] Comparative Example 1 A conventional VO2 membrane.

[0035] Comparative Example 2 A W-VO2 thin film, which differs from Example 1 in that it only includes a first functional layer, which is formed of W-VO2 material (obtained by doping W with VO2, where the doping amount of W is 1 at.%).

[0036] Comparative Example 3 A TiO2 / Mn-VO2 composite film differs from Example 1 in that it does not include a buffer layer. Otherwise, it is the same as Example 1.

[0037] Comparative Example 4 A Mn-VO2 / SiO2 composite thin film differs from Example 1 in that it does not include a second functional layer. Otherwise, it is the same as Example 1.

[0038] Comparative Example 5 A TiO2 / Mn-VO2 / SiO2 composite thin film differs from Example 1 in that the spin coating of the SiO2 precursor liquid, the first material precursor liquid, and the TiO2 precursor liquid is all done in a single step, at 3000 r / min for 30 s. Everything else is the same as in Example 1.

[0039] Test Example 1 Following the step of forming the first functional layer in the preparation method of the TiO2 / Mn-VO2 / SiO2 composite thin film of Example 1, the first functional layer (Mn-VO2) was separately prepared on a glass substrate. The XRD pattern of this first functional layer is shown below. Figure 2 As shown, the main body is monoclinic vanadium dioxide (corresponding to PDF#65-7960). The doping of Mn did not change the monoclinic crystal structure of VO2, indicating that the radii of Mn and V ions are well-matched, allowing them to stably integrate into the VO2 lattice system without causing significant lattice distortion. The SEM image of this first functional layer is shown below. Figure 3 As shown, its crystal morphology is uniform and regular; the corresponding EDS image of the SEM image is as follows. Figure 4 As shown, in addition to the characteristic peaks of V and O elements, there are also obvious characteristic peaks of Mn element. Furthermore, quantitative analysis by EDS energy dispersive spectroscopy shows that the atomic percentage of Mn element is about 1.0 at.%, which is basically consistent with the preset Mn doping amount. This confirms that Mn element has been successfully doped into VO2 lattice, and there is no local aggregation or precipitation of Mn element.

[0040] Test Example 2 The following performance tests were performed on the products prepared in the embodiments and comparative examples of this application: Phase transition temperature (Tc): Measured by differential scanning calorimetry (DSC) at a heating rate of 10℃ / min; Visible light transmittance (Tlum): Measured by a UV-Vis-IR spectrophotometer, the average value is taken in the 380nm~780nm wavelength range; Solar energy regulation efficiency (ΔTsol): Tested in the 280nm~2650nm wavelength band, and the difference in transmittance before and after the phase change was calculated; Contact angle: Tested using a contact angle meter (5μL deionized water droplet); Adhesion: Tested using the cross-cut test (ISO 2409), with grade 1 being the best and grade 5 being the worst.

[0041] The test results are shown in Table 1.

[0042] Table 1 Based on the data in Table 1, compared with Example 1, Comparative Example 1 is only a single VO2 film, which cannot achieve phase transition temperature control and synergistic performance improvement. The overall thermochromic performance, stability and practical functions are significantly degraded. Compared with Example 1, Comparative Example 2 uses traditional W doping instead of the Mn doping of the present invention and does not set a composite layer structure. Although it can reduce the phase transition temperature, due to insufficient compatibility of doping elements and lack of interface optimization and functional enhancement, the core optical and thermal performance is significantly worse than that of Example 1. Compared with Example 1, Comparative Example 3 lacks the SiO2 buffer layer of the present invention, which destroys the interface compatibility design of the composite structure, resulting in a decrease in interlayer bonding stability and thus affecting the overall performance. Compared with Example 1, Comparative Example 4 does not set the TiO2 functional layer of the present invention, and the optical performance is reduced. Compared with Example 1, Comparative Example 5 does not use the optimized two-step spin coating process of the present invention. The uneven spreading during the film forming process leads to an increase in surface defects and affects the overall performance.

[0043] In the description of this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature.

[0044] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and additions without departing from the method of the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention.

Claims

1. A TiO2 / Mn-VO2 / SiO2 composite thin film, characterized in that, It consists of a buffer layer, a first functional layer, and a second functional layer, in sequence. The buffer layer is formed of SiO2; The first functional layer is formed of a first material, which is obtained by doping Mn with VO2, wherein the doping amount of Mn is 0.8 at.% to 1.2 at.%. The second functional layer is formed of TiO2.

2. The TiO2 / Mn-VO2 / SiO2 composite thin film according to claim 1, characterized in that, The thickness of the buffer layer is 70nm~100nm, the thickness of the first functional layer is 70nm~100nm, and the thickness of the second functional layer is 70nm~100nm.

3. The method for preparing the TiO2 / Mn-VO2 / SiO2 composite thin film according to any one of claims 1 to 2, characterized in that, The SiO2 precursor solution is prepared from the SiO2 using a sol-gel method; the first material precursor solution is prepared from the first material using a sol-gel method; and the TiO2 precursor solution is prepared from the TiO2 using a sol-gel method. The preparation method includes the following steps: The SiO2 precursor liquid is spin-coated onto the surface of the substrate, and then subjected to a first annealing to form the buffer layer; The first material precursor liquid is spin-coated onto the surface of the buffer layer, and then subjected to a second annealing to form the first functional layer; The TiO2 precursor liquid is spin-coated onto the surface of the first functional layer, and then subjected to a third annealing to form the second functional layer, thereby obtaining the TiO2 / Mn-VO2 / SiO2 composite film.

4. The method for preparing the TiO2 / Mn-VO2 / SiO2 composite thin film according to claim 3, characterized in that, The spin coating of the SiO2 precursor solution includes a first spin coating and a second spin coating in sequence. The first spin coating rate is 300 r / min to 500 r / min and the first spin coating time is 6 s. The second spin coating rate is 3000 r / min to 6000 r / min and the second spin coating time is 30 s. And / or, the spin coating of the first material precursor liquid sequentially includes a third spin coating and a fourth spin coating, wherein the rate of the third spin coating is 300 r / min to 500 r / min and the time of the third spin coating is 6 s, and the rate of the fourth spin coating is 3000 r / min to 6000 r / min and the time of the fourth spin coating is 30 s. And / or, the spin coating of the TiO2 precursor liquid includes a fifth spin coating and a sixth spin coating in sequence, wherein the rate of the fifth spin coating is 300 r / min to 500 r / min and the time of the fifth spin coating is 6 s, the rate of the sixth spin coating is 3000 r / min to 6000 r / min and the time of the sixth spin coating is 30 s.

5. The method for preparing the TiO2 / Mn-VO2 / SiO2 composite thin film according to claim 3, characterized in that, The temperature of the first annealing is 400℃~550℃, and the time is 1h~2h; And / or, the temperature of the second annealing is 400℃~550℃, and the time is 1h~2h; And / or, the temperature of the third annealing is 400℃~550℃, and the time is 1h~2h.

6. The method for preparing the TiO2 / Mn-VO2 / SiO2 composite thin film according to claim 3, characterized in that, The preparation of the first material precursor solution includes the following steps: The vanadium and manganese sources were dissolved in water, and polyvinylpyrrolidone was added and stirred to obtain the precursor solution of the first material.

7. The method for preparing the TiO2 / Mn-VO2 / SiO2 composite thin film according to claim 3, characterized in that, The substrate is fixed by a chuck, and the vacuum degree of the chuck is 3×10⁻⁶. -2 Pa~2×10 -1 Pa.

8. The application of the TiO2 / Mn-VO2 / SiO2 composite thin film as described in any one of claims 1 to 2 in smart windows.